Fit to be well essential concepts / Alton L. Thygerson, Steven M. Thygerson - Thygerson, Alton L.; Thygerson, Steven M. (Jones & Bartlett Learning, 2013)
Fit to Be Well: Essential Concepts offers simple, workable approaches for being healthy and fit that can easily be integrated into a student's lifestyle and schedule. It encourages students to improve their eating habits and incorporate healthier foods into their diet; increase their level of physical activity; keep their body composition and weight at a healthy level; increase their self-esteem and create a more positive self-image; and reduce stress. Each chapter contains easy-to-follow guidelines to help students modify their lifestyle behaviors and make responsible decisions. A student lab manual is included at the back of the book at no additional cost! By adding self-assessments and related labs to each of the chapters, this text becomes an interactive guide to building and implementing a fitness program that will work with a student's individual needs and schedules.